Bibliographic Analysis of the Healthy Lifestyle Problems in the Philosophical, Psychological and Pedagogical Studies - Shvets, N. A. (Psychological Prospects Journal, 2012)
An analysis of scientific literature on the problem of the students’ healthy lifestyle formation is given in the article. History of national education on the issue of the young generation health is considered.